Thin Endometrium Is Also Associated With Lower Clinical Pregnancy Rate in Unstimulated Menstrual Cycles: A Study Based on Natural Cycle IVF - von Wolff, Michael; Fäh, Monika; Roumet, Marie; Mitter, Vera; Stute, Petra; Griesinger, Georg; Kohl Schwartz, Alexandra (Frontiers in Endocrinology, 2018)
Introduction: Does the endometrial thickness (EMT) at the time of follicle aspiration correlate with the pregnancy rate in unstimulated menstrual cycles? Materials and Methods: This is a retrospective, observational single center study.105 women with regular menstrual cycles undergoing their first NC-IVF cycle with an embryo transfer were analyzed. Clinical pregnancy and live birth rates were calculated and data were adjusted for women's age, cycle day of follicle aspiration and body mass index (BMI). Results: Age of participants was 35.0 y [32.0; 37.0]. Follicle aspiration was performed on day 14.0 [12.0; 15.0] of the cycle. Total clinical pregnancy rate was 24.8% and live birth rate 15.2% per transfer. Pregnancy rate in women with endometrial thickness ≤7 mm (n = 27) was 7.4 and 30.8% in women >7 mm (n = 78) (OR 5.56, 1.22–25.36) (P = 0.03). Live birth rates were not significantly different. Quadratic regression analysis revealed lower pregnancy rates in women with thin (around <8 mm) as well as with thick (around >11 mm) endometria. P-value after crude quadratic analysis was 0.028 and after adjustment for age, day of aspiration and BMI was 0.039. Significance was not reached for live birth rates. Conclusion: Thin endometrium should also be considered as an independent negative prognostic factor for achieving pregnancy in women without ovarian stimulation.